Viktor Nozadze and „Vepkhistkaosani (The Knight in the Panther Skin)“ - Urdulashvili, Lali (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2023)
The emigrant scientist Viktor Nozadze holds a special place among Georgian rustvelologists of the 20th century. After leaving his homeland, he lived and worked in Europe until the end of his life. Viktor Nozadze passed away in France and is buried in the Georgian cemetery of Levili. The scientific contributions of Viktor Nozadze are invaluable and remain relevant to this day. For a long time, his works were unknown to Georgian society due to economic circumstances. He was recognized only within a narrow circle of specialists as a scholar of Rustveli›s poem. Despite facing difficulties in obtaining the necessary literature abroad, V. Nozadze tirelessly collaborated with friends on translating the poem. The scientist authored encyclopedic monographs: on color speech, natural speech, solar speech, star speech, social speech, divine speech, and intimate speech. Thanks to his broad erudition and natural talent, he illuminated many obscure passages of the poem and provided his own interpretations of previously unstudied stanzas. With his works, V. Nozadze opened a completely new chapter in rustvelological science.